PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DI SEKOLAH MENENGAH - Salmiati Salmiati; Zahnur Zahnur; Rini Oktavia (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Information technology development has reached all aspects of life, including education. The use of technology in the learning process provides a big role and function for the world of education in providing interesting and easy to be accessed learning resources. This study aims to develop Android-based learning media on the lesson matrix for class XI, find the feasibility level of Android-based learning media according to validation results and find the level of acceptance of Android-based learning media in accordance with the results of testing on users. This study uses the Research and Development method. The steps include the analysis, design, development, implementation, and evaluation stages. The results showed that the learning media "SMA Matrix" is very feasible to use, this is based on the results of validation by media experts and material experts with each obtaining an average value of 4.27 (very feasible) and 4.44 (very feasible). The level of acceptance of learning media "SMA Matrix" is very highly accepted by users, this is based on the results of media testing by users who get an average value of 4.63 (very high acceptance). The based on the results of the validation and testing media, it can be concluded that the learning media "Matriks SMA" is very feasible to be used as a learning media.